Spin filter effect of manganese phthalocyanine contacted with single-walled carbon nanotube electrodes. - SANVITO, STEFANO (My University, 2010)
We present a theoretical study of the spin transport through a manganese phthalocyanine (MnPc) molecule sandwiched between two semi-infinite armchair single-walled carbon nanotube (SWCNT) electrodes. Ab initio modeling is performed by combing the nonequilibrium Green?s function formalism with spin density functional theory. Our calculations show that MnPc not only can act as a nearly perfect spin filter, but also has a large transmission around the Fermi level, which is dominated by the highest occupied molecule orbital (HOMO). The HOMO of MnPc is found to be a singly filled doubly degenerate molecular orbital, where the electrodes? Fermi level can easily pin. The spin filter effect of MnPc is very robust regardless of whether the open ends of the SWCNT electrodes are terminated by hydrogen, fluorine, or carbon dimers, demonstrating its promising applications in future molecular spintronics.
PUBLISHED
Keywords: ab initio calculations; carbon nanotubes; Nanoscience & Materials